What do patients think about the role of optometrists in providing advice about smoking and nutrition?. (March 2017) - Downie, Laura E.; Douglass, Amanda; Guest, Daryl; Keller, Peter R.
Abstract: Purpose: Tobacco smoking and nutrition are key lifestyle factors with long‐term effects on eye health. However, little is known about patients' perceptions and experiences in these areas in relation to the care received from optometrists. The main aim was to survey patients' perceptions and prior experience regarding the role of optometrists in enquiring and providing advice about tobacco smoking and nutrition. Methods: An anonymous, paper‐based survey was distributed to a convenience sample of 225 adults attending the University of Melbourne eye care clinic. Respondents provided demographic and other information (age, sex, length of time since last eye examination, country of most recent eye examination, smoking status and intake of nutritional supplements) and indicated their level of agreement (using a five‐step Likert scale) with a series of statements relating to the care provided by optometrists in the areas of health, smoking and nutrition. The statements were designed to assess the perceived scope of practice of optometrists and the extent to which patients expect, and feel comfortable, discussing these issues with their optometrist. Results: 220 completed surveys were returned. Most respondents (>80%) agreed that they visit their optometrist to quantify their refractive error and to examine their eye health. About two‐thirds of respondents indicated that they expect their optometrist to ask about their general health, with almost half expecting their optometrist to communicate with their general medical practitioner. Approximately one‐third of respondents indicated having been routinely questioned about their smoking status, diet and nutritional supplement intake by their optometrist. This was despite about half expecting their optometrist to question them about these factors and almost three out of four respondents indicating that they felt comfortable talking with their optometrist about these lifestyle behaviours. Conclusions: This study provides novel insight into patients' perceptions and experience with optometric practice in the areas of tobacco smoking and nutrition. The majority of respondents expected their optometrist to examine their eye health, ask them about their smoking and diet habits, and indicated feeling comfortable discussing these topics with their primary eye care provider. These findings suggest that brief advice interventions relating to tobacco use and diet are likely to be acceptable to deliver in optometry practice.